Use of Post-transplant Cyclophosphamide Treatment to Build a Tolerance Platform to Prevent Liquid and Solid Organ Allograft Rejection - Lightbourn, Casey O.; Wolf, Dietlinde; Copsel, Sabrina N.; Wang, Ying; Pfeiffer, Brent J.; Barreras, Henry; Bader, Cameron S.; Komanduri, Krishna V.; Perez, Victor L.; Levy, Robert B. (Frontiers in Immunology, 2021)
Corneal transplantation (CT) is the most frequent type of solid organ transplant (SOT) performed worldwide. Unfortunately, immunological rejection is the primary cause of graft failure for CT and therefore advances in immune regulation to induce tolerance remains an unmet medical need. Recently, our work and others in pre-clinical studies found that cyclophosphamide (Cy) administered after (“post-transplant”, PTCy) hematopoietic stem cell transplantation (HSCT), i.e. liquid transplants is effective for graft versus host disease prophylaxis and enhances overall survival. Importantly, within the past 10 years, PTCy has been widely adopted for clinical HSCT and the results at many centers have been extremely encouraging. The present studies found that Cy can be effectively employed to prolong the survival of SOT, specifically mouse corneal allografts. The results demonstrated that the timing of PTCy administration is critical for these CT and distinct from the kinetics employed following allogeneic HSCT. PTCy was observed to interfere with neovascularization, a process critically associated with immune rejection of corneal tissue that ensues following the loss of ocular “immune privilege”. PTCy has the potential to delete or directly suppress allo-reactive T cells and treatment here was shown to diminish T cell rejection responses. These PTCy doses were observed to spare significant levels of CD4+FoxP3+ (Tregs) which were found to be functional and could readily receive stimulating signals leading to their in vivo expansion via TNFRSF25 and CD25 agonists. In total, we posit future studies can take advantage of Cy based platforms to generate combinatorial strategies for long-term tolerance induction.